Pengaruh Pemberian Pupuk Organik Cair dari Daun Lamtoro (Leucaena leucocephala L.) terhadap Pertumbuhan Tanaman Kangkung Darat (Ipomea reptans Poir.) - Widia Putri Febriani (Pendidikan Biologi STKIP YPM Bangko, 2020)
This research is motivated by the alternative utilization of Lamtoro leaves in Merangin regency. Lamtoro leaf has potential as a liquid organic fertilizer. This study aims to determine the effect of liquid organic fertilizer from lamtoro leaves on the growth of ground water spinach plant and determine the concentration of liquid organic fertilizer from lamtoro leaves that provide the best results on the growth of ground water spinach plant. This research uses a completely randomized design (CRD) of one factor, consisting of 6 treatments namely P0 (0%), P1 (5%), P2 (10%), P3 (15%), P4 (20%), P5 (25%), with 4 replications. The parameters of this study were plant height, number of leaves, leaf serface area and root length. Data were analyzed using analysis of variance and continued with Duncan multiple range test (DMRT) at 5% level. The results showed that liquid organic fertilizer from lamtoro leaves had a significant effect on the number of leaves and root length, but did not have a significant effect on plant height and leaf surface area of ground water spinach plants. Liquid organic fertilizer from lamtoro leaves with a concentration of 5% gives the best results on the number of leaves, and a concentration of 10% gives the best results on the root length of the ground water spinach plants.